The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1097/med.0000000000000825
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and thyroid cancer risk

Abstract: Purpose of review This review explores recent evidence assessing the relationship between obesity and thyroid cancer. Recent findings Consistent evidence from observational studies suggests that obesity increases the risk of thyroid cancer. The relationship persists when alternative measures of adiposity are used, but the strength of association may vary according to the timing and duration of obesity and how obesity or other metabolic parameters are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The risk seems to be affected by gender, with women being exposed to a greater risk of differentiated thyroid cancer than men are, although a healthy body weight reduces the risk in both genders ( 55 , 56 ). Moreover, obesity is significantly associated with several adverse histological characteristics of papillary thyroid cancer at diagnosis, including larger tumor size, multifocality, extrathyroidal extension, lymph nodal involvement, and BRAF mutation ( 57 , 58 , 59 ). Several studies suggested that the leading mechanisms explaining how weight excess can affect the risk of differentiated, mostly papillary, thyroid cancer are in the pro-inflammatory background (interleukin 6 and tumor necrosis factor alpha), insulin resistance, hyperglycemia, dyslipidemia, and altered signaling of thyroid-stimulating hormone, insulin growth factor 1, leptin, adiponectin, and androgens, ultimately promoting thyroid cell proliferation ( 60 , 61 , 62 , 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…The risk seems to be affected by gender, with women being exposed to a greater risk of differentiated thyroid cancer than men are, although a healthy body weight reduces the risk in both genders ( 55 , 56 ). Moreover, obesity is significantly associated with several adverse histological characteristics of papillary thyroid cancer at diagnosis, including larger tumor size, multifocality, extrathyroidal extension, lymph nodal involvement, and BRAF mutation ( 57 , 58 , 59 ). Several studies suggested that the leading mechanisms explaining how weight excess can affect the risk of differentiated, mostly papillary, thyroid cancer are in the pro-inflammatory background (interleukin 6 and tumor necrosis factor alpha), insulin resistance, hyperglycemia, dyslipidemia, and altered signaling of thyroid-stimulating hormone, insulin growth factor 1, leptin, adiponectin, and androgens, ultimately promoting thyroid cell proliferation ( 60 , 61 , 62 , 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…The best‐studied risk factor for differentiated thyroid carcinomas is radiation exposure, which increases the risk of thyroid malignancy from 5% to 50%. 17 , 22 Other risk factors include estrogen, 23 smoking, 24 diabetes, 25 insulin resistance, 26 obesity, 27 metabolic syndrome , 28 insulin resistance, 23 and physical activity. 29 In a population‐based cohort study conducted in Korea, smoking and alcohol were shown to be inversely associated with thyroid cancer, with a significant interaction between these variables.…”
Section: Discussionmentioning
confidence: 99%